Efektivitas Penerapan Elevasi Kepala terhadap Peningkatan Perfusi Jaringan Otak pada Pasien Stroke - Logi Kiswanto; Nur Chayati (Journal of Telenursing (JOTING), 2021)
This study aims to determine the effect of applying head elevation to improve cerebral tissue perfusion in stroke patients. The method used is a single data, namely a literature review. The results showed that 30° head elevation was recommended in improving cerebral tissue perfusion, although the difference was not too high. In conclusion, there is an effect of the SPO2 value after the head elevation is 30°, and 15° in stroke patients. Keywords: Head Elevation, Cerebral Perfusion, Stroke